Proposed pedestrian pathway roughness thresholds to ensure safety and comfort for wheelchair users. Issue 4 (1st October 2016) - Duvall, Jonathan; Sinagra, Eric; Cooper, Rory; Pearlman, Jonathan
ABSTRACT: In the United States, over three million people use a wheelchair for their primary means of mobility and they rely on functional and accessible pathways to participate in their communities. The Americans with Disabilities Act Accessibility Guidelines related to pathway roughness are currently ambiguous, subjective and therefore unable to be measured. Consequently, many public pathways are sufficiently rough to result in harmful vibrations and discomfort for wheelchair users. In previous research, subjective ratings and root-mean-square accelerations were reported from subjects traveling over surfaces with various roughnesses in their own wheelchairs. The purpose of the current study is to use previous data to propose roughness thresholds by correlating the roughness of surfaces to vibration data and subjective ratings from wheelchair users. The results suggest a pathway roughness index threshold of ≤50 mm/m (1.2 in./ft) for a surface segment of 100 m (328 ft) in length, and ≤100 mm/m (1.2 in./ft) for a surface segment of 3 m (9.8 ft) in length would protect wheelchair users against discomfort and possible health risks due to vibration exposure. For surfaces of different lengths, a 3 m (9.8 ft) and 100 m (328 ft) moving window should be used.